Combining hydrodynamic modelling with genetics: can passive larval drift shape the genetic structure of Baltic Mytilus populations?. Issue 10 (4th April 2017) - Stuckas, Heiko; Knöbel, Loreen; Schade, Hanna; Breusing, Corinna; Hinrichsen, Hans‐Harald; Bartel, Manuela; Langguth, Klaudia; Melzner, Frank
Abstract: While secondary contact between Mytilus edulis and Mytilus trossulus in North America results in mosaic hybrid zone formation, both species form a hybrid swarm in the Baltic. Despite pervasive gene flow, Baltic Mytilus species maintain substantial genetic and phenotypic differentiation. Exploring mechanisms underlying the contrasting genetic composition in Baltic Mytilus species will allow insights into processes such as speciation or adaptation to extremely low salinity. Previous studies in the Baltic indicated that only weak interspecific reproductive barriers exist and discussed the putative role of adaptation to environmental conditions. Using a combination of hydrodynamic modelling and multilocus genotyping, we investigate how oceanographic conditions influence passive larval dispersal and hybrid swarm formation in the Baltic. By combining our analyses with previous knowledge, we show a genetic transition of Baltic Mytilus species along longitude 12°‐13°E, that is a virtual line between Malmö (Sweden) and Stralsund (Germany). Although larval transport only occurs over short distances (10–30 km), limited larval dispersal could not explain the position of this genetic transition zone. Instead, the genetic transition zone is located at the area of maximum salinity change (15–10 psu). Thus, we argue that selection results in weak reproductive barriers and local adaptation. This scenario could maintain genetic and phenotypic differences between Baltic Mytilus species despite pervasive introgressive hybridization.